Ergosterol purification from basidiomes of Clouded Agaric (Clitocybe nebularis (Fr.) Kumm.) - V. O. Antonyuk (Zaporozhye State Medical University, 2014)
Ergosterol (ergosta-5 ,7,22-trien-3β-ol ) is a compound found only in fungi. Ergosterol has medical interest, as it is easily converted into Vitamin D2. In the previous work we have studied 22 species of true fungi. The highest quantity of ergosterol was found in basidiomes of Clouded Agaric (Clitocybe nebularis (Fr.) Kumm). Meanwhile, there is no data on the purification of ergosterol from this fungus in the literature. The aim of research. The aim of research is to elaborate a rational method of obtaining ergosterol from basidiomes of Clouded Agaric and assess the perspectives of the raw material for its purification. Materials and methods. In order to choose the best method of ergosterol purification, it was obtained in two ways: 1 ) by alkaline hydrolisis that was used in the preparation of ergosterol from baker yeast and 2) by the extraction of raw matherial by methanol with following chromatography on silica gel. A substance with high ergosterol level was purified from marc basidiomes of Clouded Agaric by methanol extraction with following of freezing the methanol extract and the following chromatography on silica gel. This substance was dissolved in hexane and purified by chromatography on silica gel by washing the column sequentially with hexane, hexane - ethyl acetate (6:1 ), hexane -ethyl acetate -methanol 4:2:1. The obtained fractions were dried and weighed. The analysis of the obtained compounds was carried out by gas-liquid сhromatography - mass spectrometry , Lieberman-Burchard reaction and TLC on silica gel. Chromatograms were spraied with saturated sodium antimony in chloroform. Results and discussion Pure ergosterol was obtained from dried baker's yeast and basidiomes marc of Clouded Agaric by alkaline hydrolysis followed by methylene chloride extraction of raw material and crystallization from ethanol and mixtures of benzene with ethanol (yield 0.71% and 0.52% ). Methanol extraction of dried basidiomes marc of Clouded Agaric, concentration and freezing, helped to obtain the substance, which according to the GLC -MS contained up to 91.1% of ergosterol. Chromatography of the substance obtained on silica gel allowed to obtain pure ergosterol with minor losses and higher purity, than by the crystallization. Conclusions We found a high content of ergosterol in Clouded Agaric basidiomes using gas-liquid chromatography-mass spectrometry. Almost pure ergosterol was sedimented by freezing of methanol extract. Authentic sample of ergosterol obtained from baker's yeast by TLC confirmed the identification of Clitocybe nebularis ergosterol. It was shown that chromatographic purification on a column of silica gel had advantages over alkaline hydrolysis of raw matherial and allowed to obtain pure ergosterol in a single stage with a higher yield (2.54 % of pure ergosterol). This method of purification is also an opportunity to obtain other substances which are in the methanol extract.